Loyalty Dynamics in Mangrove Ecotourism: Exploring the Influence of Attitudes, Perceived Benefits, Costs, and Environmental Concern - Seperi, Yuli; Sakti, Guntur (Jurnal Internasional Penelitian Bisnis Terapan, 2024)
Tourists' environmental concern acts as a catalyst, fostering a green attitude and elevating ecotourism as a primary attraction. Indonesia's vast mangrove forests offer unique opportunities for ecotourism development, given their rich biodiversity and critical role in oxygen production. This study aims to explore the intricate relationship between mangrove ecotourism and tourists' loyalty intentions and behaviors, focusing on Millennials (Gen Y) and Generation Z in urban centers like Batam City, Tanjungpinang City, and Bintan Regency in the Riau Islands Province. Utilizing quantitative methods, data from 420 respondents were collected via electronic surveys and analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The findings highlight significant relationships: perceived cost and environmental concern strongly influence tourists' green attitude while perceived benefits do not directly impact it. Perceived benefits, perceived costs, and green attitudes significantly shape loyalty intentions, with environmental concern emerging as a key driver. Additionally, loyalty intentions significantly impact perceived benefits, green attitudes, and perceived costs. Although environmental concern, perceived benefits, perceived costs, and green attitude have a significant influence on loyalty behavior, their impact is indirect. This suggests a nuanced interplay among these variables in shaping tourists' behavior in the mangrove ecotourism context, underscoring the complex dynamics at play in sustainable tourism development.